LEGAL PROTECTION OF INDIGENOUS INSTITUTIONS IN THE FRAME OF THE RULE OF LAW (PERSPECTIVE OF LEGAL PROTECTION THEORY) - Safrin Salam (Universitas Lampung, 2023)
Indigenous institutions in Indonesia are a local wisdom inherited from the ancestors of the Indonesian State. This research is normative legal research, namely legal research conducted by researching and examining statutory regulations, starting from Article 18b paragraph 2 of the 1945 Constitution, 18B paragraph (2), Article 28D paragraph (1), Article 28G paragraph (1), and Article 28I paragraph (3), and the organic regulations under them. The results of the study show that the arrangements for protecting traditional institutions in Indonesia, namely that the State is obliged to protect the natural rights of humans themselves, namely customary law communities, are based on the Decision of the constitutional court no. 35/puu/ix/2012, namely customary rights in both private law and public law. John Locke's theory of protection is related to regulations issued by the State to provide legal protection for rechtgemeschappen, which needs to be studied juridically and sociologically. While the harmonization of customary institutional protection norms in Indonesia, namely by carrying out a legal review (reviewing) of legal regulations against Permendagri with Article 18b, Paragraph 2 of the 1945 Constitution, Article 6 of Law Number 39 of 1999 concerning human rights, Constitutional Court Decision Number 35/puu-ix/2012 Permendagri Number 52 of 2014 concerning the recognition and protection of customary law communities, and Circular Letter Number 3/se/iv/2014 regarding the determination of the existence of customary law communities and ulayat lands.